ANALISIS PENGGUNAAN MEDIA GUTA (GAME ULAR TANGGA) DALAM PEMBELAJARAN MATEMATIKA KELAS V SD - Elin Julianti (Al-mujahidah, 2024)
Some errors that occur in the learning process are the teacher's lack of effectiveness in using learning media. This results in learning mathematics becoming boring and not of interest to students. So here it is necessary to apply a variety of learning media in mathematics learning, such as the use of snakes and ladders media in mathematics learning. This research aims to analyze and describe the use of Snakes and Ladders Media in mathematics learning. This research method uses a qualitative descriptive method with the variable in this research being the scope of mathematics learning content. Documents used include teacher books and student books. The methods used in collecting data are observation, experimentation and pretest-posttest techniques. The data from this research were then analyzed using qualitative descriptive methods. The research subjects were objects, namely the snakes and ladders game media and 5th grade elementary school mathematics learning student books. The research subjects of the informants were: Principal, Class 5 Teacher and 30 Class 5 students. With pretest scoring results of 23% before using the media and post test scoring results of 50% after using the media, so there was an increase in scoring results of 27%.